Impact of inverter-based generation on islanding detection schemes in distribution networks - Markovic, Uros; Chrysostomou, Demetris; Aristidou, Petros; Hug, Gabriela (My University, 2021)
One of the most frequently used interface protections for Distributed Generators (DGs) is the Loss of Mains (LoM) protection. It detects the formation of an island at the connection point and disconnects the DG to protect the unit, the system and the personnel. The increased penetration of inverter-interfaced DG, in combination with the decommissioning of synchronous generators, reduces the system inertia and leads to faster changing and larger voltage and frequency deviations. Therefore, modern grid-codes require inverter-based DGs to provide support to the grid by modifying their active and reactive power injection based on local measurements. However, this leads to complex inverter-grid interactions and modifies the islanded system behavior, thus disturbing the operation of LoM protections that rely mainly on local voltage and frequency measurements. In this paper, we propose an improved analytical formulation for estimating the Non-Detection Zone (NDZ) of LoM protection devices in the presence of grid-feeding inverters, as well as novel NDZ approximations for grid-supporting and grid-forming inverter-based services. We verify the analytical results with detailed dynamic simulations and comment on the impact that the new inverter requirements have on the performance of LoM protections.
Keywords: Non-detection zone; Loss of mains; Analytical approximation; Grid-forming; Grid-following